Urbanização e cidades: análises da microrregião de Ituiutaba (MG) - Oliveira, Hélio Carlos Miranda de (2013)
The aim of this study was to understand urbanization process and and the socio-spatial formation of the municipalities and the cities of the Geographic Microrregion (MRG) of Ituiutaba (MG), which is located in the northwestern part of the Triângulo Mineiro, in the state of Minas Gerais, and it is consisted by six municipalities/cities: Cachoeira Dourada (MG), Capinópolis (MG), Gurinhatã (MG), Ipiaçu (MG), Ituiutaba (MG) e Santa Vitória (MG). The urbanization and the dynamics of the cities was investigated with an analytical focus on economic relations, understanding that such relationships provide common elements that allow evaluate the MRG surveyed in its entirety. Once it is inserted in a broader spatial context, the territorial occupation of the brazilian savannah and the urbanization of the Triângulo Mineiro, it is important the analysis of the MRG regarding the spatial dynamics inserted in the Triângulo Mineiro, as well as the territorial and economic formation process. The investigations exceeded the cities boundaries and it was considered both the economy and spatial relationship of the municipalities, once it is impossible to understand the process of urbanization and the urban dynamics in the recent MRG Ituiutaba (MG) without reflecting on the influence of agricultural production in the urban and the cities (re) structuration. Then resorted to the understanding of socio-spatial formation, in order to apprehend the particularities of the urbanization process in time, as their changes and contemporary content. Thereby, the intra-urban space was studied in the economic and social perspective of the city, seeking to identify the recent urban dynamics as well as the action of new economic agents.